The Infraorder Coccomorpha (Insecta: Hemiptera) - Hodgson, Chris; Denno, Barb; Watson, Gillian W. (Zootaxa, 2021)
The scale insects (infraorder Coccomorpha) are the most morphologically specialised members of the Hemiptera. They form a monophyletic group within the suborder Sternorrhyncha, having one-segmented tarsi and a single claw (all other hemipterans have a double claw). They show extreme sexual dimorphism: the more-or-less sessile adult females are wingless and larviform, whereas the motile adult males mostly are winged and lack mouthparts. Within the Coccomorpha, 54 families are currently recognised, of which 20 are known only from fossils and 34 are extant (García Morales et al. 2016).